(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Nontraditional risk factors for cardiovascular disease (CVD), including mineral disorder, high fibroblast growth factor 23 (FGF23), low klotho, and low soluble TWEAK could predict the incipient risk of CVD in chronic kidney disease (CKD). The present study evaluates the effect of sevelamer on soluble tumor necrosis factor-like weak inducer of apoptosis (TWEAK), and klotho levels in adenine-induced CKD rats. Methods and Materials. Normal control rats without sevelamer were compared with 3 groups of adenine-induced CKD rats, including CKD rats without sevelamer, CKD rats treated with 3% sevelamer, and rats receiving adenine and 3% sevelamer concurrently. After 4 weeks of sevelamer treatment, serum levels of klotho and soluble TWEAK were measured, along with biochemical parameters related to kidney function. Results. Sevelamer significantly reduced serum levels of phosphate and increased serum levels of klotho and soluble TWEAK. Decreased levels of phosphate were negatively correlated with elevated levels of klotho and soluble TWEAK (r = -0.70, P = .003; r = -0.58, P = .02; respectively) in serum. Conclusions. Sevelamer successfully reduced serum levels of phosphate, and meanwhile, it led to an elevation in serum levels of klotho and soluble TWEAK in rat models of CKD.